2010
DOI: 10.1111/j.1464-5491.2009.02869.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish‐oil supplement has neutral effects on vascular and metabolic function but improves renal function in patients with Type 2 diabetes mellitus

Abstract: This study demonstrated that 12 weeks of fish-oil supplement had no significant beneficial effect on vascular endothelial function, but improved renal function without changes in endothelial function, metabolic profiles, blood pressure, inflammation or oxidative stress in patients with Type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 44 publications
3
60
3
Order By: Relevance
“…In contrast to the observational studies showing that EPA-DHA may prevent or slow down the decline of kidney function, clinical trials show conflicting results (31)(32)(33)(34). However, a trial in patients with type 2 diabetes (n=97) showed, after 3 months of supplementation with 4 g fish oil/d, 0.05 mg/dl lower serum cr compared with controls (35). A meta-analysis, including 626 patients from 12 trials with predominantly IgA nephropathy and diabetes, showed that 0.7-5.1 g/d fish oil supplementation compared with placebo resulted in an 11% (95% CI, 27% to 29%) slower decline of kidney after a median follow-up of 9 months (36).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the observational studies showing that EPA-DHA may prevent or slow down the decline of kidney function, clinical trials show conflicting results (31)(32)(33)(34). However, a trial in patients with type 2 diabetes (n=97) showed, after 3 months of supplementation with 4 g fish oil/d, 0.05 mg/dl lower serum cr compared with controls (35). A meta-analysis, including 626 patients from 12 trials with predominantly IgA nephropathy and diabetes, showed that 0.7-5.1 g/d fish oil supplementation compared with placebo resulted in an 11% (95% CI, 27% to 29%) slower decline of kidney after a median follow-up of 9 months (36).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the n-3s found in fatty fish such as salmon, trout and mackerel are the long-chain polyunsaturated fatty acids (PUFAs) eicosapentaneoic acid (EPA) and docosahexaneoic acid (DHA), consisting of 20 and 22 carbons, respectively. Much of the literature supporting the benefits of n-3s for CVD risk reduction has been conducted on EPA and DHA, showing improvements in triglyceride levels in both healthy participants and those with elevated triglyceride levels (163)(164)(165). While the body does convert some dietary ALA into EPA and DHA, evidence suggests the conversion rate is poor, estimated at <5% depending on n-6 intake (166).…”
Section: Dietary Fatmentioning
confidence: 99%
“…Omega-3 fatty acids derived from marine fish oil predominantly lower triglycerides, but may also have beneficial effects on HDL subfractions and LDL-particle size, as well as direct actions on the vasculature to reduce inflammation and endothelial cell activation [152]. In randomized, double-blind, controlled trials in T2D patients, omega-3 fatty acid supplementation improved acetylchollilne (Ach)-stimulated FABF [153], but not fasting brachial artery FMD [154,155]. Compared with placebo, 6 weeks of purified eicosapentenoic acid (EPA)/docosahexemoic acid (DHA) (2g/day) significantly reduced the postprandial decrease in FMD and improved postprandial microvascular function in T2D patients [156].…”
Section: Lipid-regulating Therapymentioning
confidence: 99%